Study guides

☆☆

Q: What is 7a plus 3b minus 5a minus 2b minus b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

-2a plus 3b

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

8a+2b

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

Gathering like terms together, this is equal to 5a + 3b + 7c.

Related questions

-2a plus 3b

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus

8a+2b

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

Gathering like terms together, this is equal to 5a + 3b + 7c.

5a(2b + 1)

-6(a-3b-9c)

6+7a+6b

no

6a+7b

The given expression can be simplified to: 3b-a

People also asked